2019
DOI: 10.1038/s41598-018-36449-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical characterization of TIM protein–mediated Ebola virus–host cell adhesion

Abstract: Since the most recent outbreak, the Ebola virus (EBOV) epidemic remains one of the world’s public health and safety concerns. EBOV is a negative-sense RNA virus that can infect humans and non-human primates, and causes hemorrhagic fever. It has been proposed that the T-cell immunoglobulin and mucin domain (TIM) family proteins act as cell surface receptors for EBOV, and that the interaction between TIM and phosphatidylserine (PS) on the surface of EBOV mediates the EBOV–host cell attachment. Despite these init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 71 publications
(93 reference statements)
2
29
0
Order By: Relevance
“…Similar to Tim-1, residues in the PS binding pocket of murine and human Tim-4 were found to be important for Ebola virus (EBOV) entry, and additional Tim-4-specific residues were also found to impact virion binding and internalization, which provided a greater understanding of the interaction between Tim-4 and EBOV virions (84). Interestingly, Tim-EBOV interactions were mechanically comparable to adhesion molecule-ligand interactions and the Tim-4-PS interaction was more resistant to mechanical force than the Tim-1-PS interaction (85). Exosomes from multiple sources increased HIV-1 entry into T cells and macrophages, and viral entry was potently blocked with anti-Tim-4 antibodies (86).…”
Section: Pathogen Infectionmentioning
confidence: 99%
“…Similar to Tim-1, residues in the PS binding pocket of murine and human Tim-4 were found to be important for Ebola virus (EBOV) entry, and additional Tim-4-specific residues were also found to impact virion binding and internalization, which provided a greater understanding of the interaction between Tim-4 and EBOV virions (84). Interestingly, Tim-EBOV interactions were mechanically comparable to adhesion molecule-ligand interactions and the Tim-4-PS interaction was more resistant to mechanical force than the Tim-1-PS interaction (85). Exosomes from multiple sources increased HIV-1 entry into T cells and macrophages, and viral entry was potently blocked with anti-Tim-4 antibodies (86).…”
Section: Pathogen Infectionmentioning
confidence: 99%
“…Gaertner and Massberg, in their fascinating review on immunothrombosis, have also advocated that fibrin forms a trap for invading pathogens and provides the recruitment of immune effector cells, a now recognized important defence mechanism in innate immunity while uncontrolled immunothrombosis can lead to disseminated intravascular coagulation [12]. Morera et al have also shown that erythrocytes may have a direct role in the immune response [13] while Dragovich et al recently demonstrated that cell membrane tension and stiffness might be the dominant defense against Ebola attachment to host cell in an atomic force model [14]. Could this play a role here in the adaptation of the immune response of SCD patients to COVID‐19?…”
Section: Patient 1 2mentioning
confidence: 99%
“…We believe that the force-displacement results can be related directly to the atomic force microscopy (AFM) force-displacement measurements. 18 19,20…”
Section: Discussionmentioning
confidence: 99%
“…This is of interest because such analyses can be used to interpret in detail atomic force microscopy (AFM) force-spectroscopy measurements of force-deflection response used to characterize the adhesion process 17 , particularly to interpret the force-spectroscopy studies on virus–host cell interactions. 1820 It is also of interest because virus attachment often occurs under external load, which is accounted for in a contact mechanics model but not in most of the literature cited above. In this work, we create a continuum model for the small-deflection adhesive contact mechanics of virus particle attachment onto the host cell membrane in terms of the principal biophysical properties of the virus, membrane, and their interaction.…”
Section: Introductionmentioning
confidence: 99%